Penambahan Sekam Padi Mentah, Sekam Padi Bakar, dan Daun Kering terhadap Kualitas Fisik dan Kimia Kompos dari Kotoran Kerbau - Juherah, Juherah; Rafidah, Rafidah; Lapik, Arnita Resty (Sulolipu: Media Komunikasi Sivitas Akademika dan Masyarakat, 2024)
The addition of materials such as raw rice husks and burnt rice husks to buffalo manure and dry leaves as compost. The incorporation of raw rice husks, burnt rice husks, and dry leaves into buffalo manure as compost. The production of compost from buffalo manure with the addition of rice husks and dry leaves can address environmental pollution caused by the organic waste of unused rice husks and dry leaves. The results of the decomposition process can also be utilized as organic fertilizer for plants. The type of research used in this study is quasi-experimental designs with three replications, employing the Kruskal-Wallis statistical test on samples of buffalo dung waste, using a comparison of raw rice husks and burned rice husks to obtain compost from buffalo dung with the best quality. The samples in this study consist of solid waste in the form of buffalo feces and organic waste in the form of raw rice husks, burned rice husks, and dry leaves obtained from Perindingan Village, Gandang Batu Sillanan District, Tana Toraja Regency. The research results on compost with the addition of raw rice husks and burned rice husks meet the quality standards of compost SNI 19-7030-2004 and show no significant differences, as compost using raw rice husks requires a decomposition time of 20 days, while compost with the addition of burned rice husks can decompose in 19 days. Both types have a crumbly and somewhat coarse texture, a soil-like smell, and are dark brown in color for compost with raw rice husks and black for compost with burned rice husks. The nitrogen (N) content is 0.53% and phosphorus (P2O5) is 0.46% in compost with raw rice husks, while the burned variety has nitrogen (N) at 0.54% and phosphorus (P2O5) at 0.94%. The conclusion of this study is that the addition of raw rice husks in the composting process is very effective because raw rice husks contain nutrients that are beneficial for plants and decompose easily. Keywords: Compost; buffalo manure; raw rice husk; fired rice husk; dry leaves